Studies of carbon cluster formation mechanism : graphene and transition adatoms - Tang, Kim Sua. (2012)
The purpose of this project was to investigate the interaction of transition metal adatoms and their effect on graphene via computer simulation. The study is based on the favoured position of the transition metal adatom on the graphene carbon network, looking at parameters such as binding energy, overall energy of the system and the distance of the adatom to the graphene. 13 transition metals were selected for the study, namely: Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Pd, Pt, Cu, Au, Zn.